KONTRIBUSI KINERJA KEUANGAN YANG MEMPENGARUHI PROFITABILITAS PERUSAHAAN BUMN - Dewi Maya Sari; Meutia Handayani (Universitas Teuku Umar, 2020)
This study aims to determine the effect of asset management, liquidity, and leverage on the profitability of BUMN companies. The data used is the 2016-2018 annual financial report data for BUMN companies. This research is a quantitative study using secondary data, namely financial statement data and the research sample is 13 companies with a period of three years 2016-2018 selected through sample criteria. Data analysis was performed using multiple linear regression methods with the help of Eviews 11 program. `The results showed that asset management and liquidity partially had no a significant effect on profitability, while leverage partially had effect on profitability. Simultenaously, it showed that asset management, liquidity, leverage affected on profitability.